Gender differences in wages and leadership - Mario Macis (IZA World of Labor, 2017)
Gender wage gaps and women's underrepresentation in leadership positions exist at remarkably similar magnitudes across countries at all levels of income per capita. Women's educational attainment and labor market participation have improved, but this has been insufficient to close the gaps. A combination of economic forces, cultural and social norms, discrimination, and unequal legal rights appear to be contributing to gender inequality. A range of policy options (such as quotas) have been implemented in some countries; some have been successful, whereas for others the effects are still unclear.
Keywords: J1; J3; 330; gender discrimination; gender wage gaps; female leadership; economic development